Guía de práctica clínica colombiana para el tratamiento de infecciones bacterianas de piel y tejidos blandos superficiales en Población pediátrica - Iván Felipe Gutiérrez-Tobar (Asociación Colombiana de Infectología, 2023)
In 2019, the practice guideline for the diagnosis and management of skin and soft tissue infections in Colombia was published. This guideline excluded the pe-diatric population because of special considerations regarding their care. Taking into account that these infections represent a frequent reason for consultation in pediatrics and that the emergence of methicillin-resistant Staphylococcus aureus increases there is a need to update knowledge and strategies for the management of superficial skin and soft tissue infections. Hence, we present this clinical practice guideline which provides evidence-based answers to 12 key questions. This evidence was adapted and graded using the GRADE system after an adaptation process of three published guidelines. Additionally, an update of the scientific evidence was carried out by means of a systematic review. Finally, we carried out an expert consensus to evaluate the potential barriers to the implementation of the recommendations in the local context.